A New Approach for Allocating a New Party's Budget during an Election Campaign - Irit Talmor; Osnat Akirav (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
During pre-election campaigns, parties make great efforts to persuade constituents to vote for them. Usually, new parties have smaller budgets and fewer resources than veteran parties. Generally, the more heterogeneous the party’s electorate, the more critical the issue of resource allocation. This paper presents a method for new parties to efficiently allocate campaign advertising resources and maximise voters. The model developed uses the Pareto principle and multi-criteria approach, integrating the party’s confidential data together with official open-to-all data. We implemented the model on a specific new party during the intensive political period before the April 2019 elections in Israel, finding that the model produced clear and unbiased results, and this made it effective and user-friendly for strategy teams and campaign managers.